Challenging the Unitary Self: Adult Education, Feminist Theory, and Nonunitary Subjectivity - Clark, Carolyn (Canadian Journal for the Study of Adult Education, 1999)
As the millennium comes to a close, the sociocultural influences of the mid 1900s that shaped the unitary model of self have changed. In this article the possibilities of a nonunitary model of the self in adult education are examined. From two parallel strands, the theoretical and the personal, I argue that a nonunitary model is better suited to catch the full complexity of human experience. Possible implications for adult education theory and practice are explored. Résumé En cette fin de millénaire, on constate l'éclatement des influences socioculturelles ayant donné lieu au modèle unitaire du moi vers le milieu du XIXème siècle. Dans cet article, j'analyse la possibilité d'un moi non unitaire en éducation des adultes, selon deux points de vue, l'un théorique et l'autre personnel. Je soutiens que la complexité de l'expérience humaine est mieux cernée par un modèle non unitaire de l'identité humaine. Ce constat comporte également des conséquences théoriques et pratiques.